Systematic Literature Review on Metaverse Library - Johan, Riche Cynthia; Ardiansah; Damayanti; Suhardini, Dini (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The development of technology and information has now gone digital with the emergence of the meta-world or metaverse. Libraries as evolving organisms need to adapt to keep up with the times and meet the needs of their patrons. This study aims to determine the extent to which research related to metaverse libraries has been carried out and how libraries can answer the challenges of digital technology developments related to metaverse technology. The method used in this research is a Systematic Literature Review using the Publish or Perish and Vos Viewer applications with the period publication analysis from the years 2014-2023. The results showed that articles related to the metaverse library are still very limited when compared to articles that discuss the metaverse itself. On the other hand, libraries are expected to continue to develop with the concept of Metaverse Library with consideration as a form of innovation to improve immersive learning, accessibility, information preservation, and collaboration globally.